2018
DOI: 10.3390/ijms19103280
|View full text |Cite
|
Sign up to set email alerts
|

Cepharanthine Enhances TRAIL-Mediated Apoptosis Through STAMBPL1-Mediated Downregulation of Survivin Expression in Renal Carcinoma Cells

Abstract: Cepharanthine (CEP) is a natural plant alkaloid, and has anti-inflammatory, antineoplastic, antioxidative and anticancer properties. In this study, we investigated whether CEP could sensitize renal carcinoma Caki cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis. CEP alone and TRAIL alone had no effect on apoptosis. However, combined CEP and TRAIL treatment markedly enhanced apoptotic cell death in cancer cells, but not in normal cells. CEP induced downregulation of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) functions as a selective apoptosis-inducing ligand in cancer cells with normal cells remaining unaffected. CEP enhances TRAIL-mediated apoptosis through a down-regulation of survivin expression, not by direct inhibition of survivin mRNA expression but via a downregulation of a deubiquitin protein that modulates survivin expression in renal carcinoma cells (Shahriyar et al, 2018).…”
Section: Anti-cancer Activity Of Cep In Drug Combinationsmentioning
confidence: 97%
“…Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) functions as a selective apoptosis-inducing ligand in cancer cells with normal cells remaining unaffected. CEP enhances TRAIL-mediated apoptosis through a down-regulation of survivin expression, not by direct inhibition of survivin mRNA expression but via a downregulation of a deubiquitin protein that modulates survivin expression in renal carcinoma cells (Shahriyar et al, 2018).…”
Section: Anti-cancer Activity Of Cep In Drug Combinationsmentioning
confidence: 97%
“…Cepharanthine dose-dependently downregulated STAMBPL1 and increased USP53 expression. Ectopic expression of STAMBPL1 significantly inhibited cepharanthine-induced reduction in the levels of survivin [43]. Overall, these findings clearly suggest that cepharanthine enhances TRAIL-induced apoptosis by promoting the degradation of survivin through STAMBPL1 downregulation in renal carcinoma cells (Figure 3).…”
Section: Natural-product-mediated Restoration Of Trail-mediated Apmentioning
confidence: 86%
“…Cepharanthine, a biscoclaurine alkaloid isolated from Stephania cepharantha , has been shown to be effective against renal carcinoma cells [43]. Cepharanthine time-dependently induced the downregulation of survivin protein levels.…”
Section: Natural-product-mediated Restoration Of Trail-mediated Apmentioning
confidence: 99%
“…In addition, STAMBPL1 stabilizes the human T-cell leukemia virus type 1 (HTLV-1) Tax oncoprotein [33]. Recently, we reported the depletion of STAMBPL1 increases apoptotic cell death through accumulation of intracellular ROS and lysosome-dependent XIAP degradation in prostate cancer cells [34], and we also reported that levels of STAMBPL1 is correlated with the expression of survivin in cepharanthine treated renal cancer cells [35]. However, the functions of STAMBPL1 and target proteins have not yet been understood.…”
Section: Introductionmentioning
confidence: 85%
“…However, honokiol had no effect on expression of USP8 in renal carcinoma Caki cells ( Figure 5B). In case of survivin, USP9X and STAMBPL1 modulate survivin expression by long noncoding RNA (lncRNA) LNC473 and cepharanthine, respectively [35,61]. LNC473 directly bind survivin and USP9X, and USP9X inhibits ubiquitination of survivin [61].…”
Section: Discussionmentioning
confidence: 99%